2016
DOI: 10.1063/1.4971325
|View full text |Cite
|
Sign up to set email alerts
|

Development of array piezoelectric fingers towards in vivo breast tumor detection

Abstract: We have investigated the development of a handheld 4 × 1 piezoelectric finger (PEF) array breast tumor detector system towards in vivo patient testing, particularly, on how the duration of the DC applied voltage, the depression depth of the handheld unit, and breast density affect the PEF detection sensitivity on 40 patients. The tests were blinded and carried out in four phases: with DC voltage durations 5, 3, 2, to 0.8 s corresponding to scanning a quadrant, a half, a whole breast, and both breasts within 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Piezoelectric immunosensors have been developed to identify specific antibody immunity in breast cancer patents. Xu et al [ 15 ] developed a piezoelectric finger (PEF) for identifying breast cancer and tested it on human subjects. In their study, PEF detected 94% of all tumors and 93% of malignant tumors, while mammography detected 91% of all tumors and 80% of malignant tumors.…”
Section: Biomarkers For Breast Cancer Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezoelectric immunosensors have been developed to identify specific antibody immunity in breast cancer patents. Xu et al [ 15 ] developed a piezoelectric finger (PEF) for identifying breast cancer and tested it on human subjects. In their study, PEF detected 94% of all tumors and 93% of malignant tumors, while mammography detected 91% of all tumors and 80% of malignant tumors.…”
Section: Biomarkers For Breast Cancer Detectionmentioning
confidence: 99%
“…Several MI methods have been developed and evaluated in numerical and experimental settings. Recent clinical studies suggested that investigators should perhaps pay more attention to the development of MI prototypes for clinical environment with particular focus on high sensitivity radio frequency (RF) sensors and sensor arrays [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The smallest tumor detected by the PEF was 2 mm × 5 mm. 39,40 Furthermore, our previous model tissue studies have also shown that the detectable depth by a PEF was approximately twice that of the probe size of the PEF. 37,40 In other words, with a larger probe size, a PEF can assess the elastic response of the tissue at a larger depth.…”
Section: Articlementioning
confidence: 87%
“…39,40 Furthermore, our previous model tissue studies have also shown that the detectable depth by a PEF was approximately twice that of the probe size of the PEF. 37,40 In other words, with a larger probe size, a PEF can assess the elastic response of the tissue at a larger depth. It is therefore possible to use a set of PEFs each with a different probe size to do the elastic modulus measurements on the same tissue and use the obtained results to deduce the tissue elastic modulus profile in the depth direction without the need of any inversion simulations.…”
Section: Articlementioning
confidence: 87%
See 1 more Smart Citation